The Influence Of Financial Literacy And Lifestyle On Financial Management In Housewives In The Moment Of Ramadan 1444 H - La Idrus*, Windi; Bailusy, Muhsin N; Hadady, E Hartaty; Amiro, Suratno (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to examine the relationship between financial literacy and lifestyle on the financial management of housewives and to find out the differences in financial literacy, lifestyle and financial management of housewives. This research is a quantitative research with data collection techniques using a questionnaire. The sample used was 85 fitu village housewives at Moment Ramadhan 1444 H, this study used the Nonprobability Sampling method. Data analysis techniques using validity, reliability, requirements analysis test, t test, and F test. The results of this study are that the financial literacy variable has no effect on the financial management of housewives. Meanwhile, lifestyle variables affect the financial management of housewives.